Reconocemos las características corporales - Ecca Vega, Carola Eliana (2018)
The present work of professional sufficiency considers the area of science and technology, as an area of formation of scientific and investigative attitudes. Part of context situations. It contributes to the formation of positive attitudes of coexistence and basic scientific and technological training, so that students are able to make decisions based on knowledge and assume responsibilities when carrying out actions that have an impact on the environment and health of the community. This work is intended to demonstrate strategies of the learning session called: We know the sense organs, their functions and care. The foundation of the Science and Technology area is also exposed according to the learning paths, the theoretical support taking into account the definition of the topic - The senses. It also shows the description of the theoretical and pedagogical support referred to the psychopedagogical, pedagogical principles such as Piaget, Novak and Ausubel, pedagogical, technical, media and material processes in the methodological process, as well as diagnostic, formative and summative evaluation and the procedures evaluation instruments